Transformasi Digital Perbankan: Implikasi Kualitas Layanan terhadap Loyalitas Pelanggan - Noventa, Oscar Chrismadian (Reviu Akuntansi, Manajemen, dan Bisnis, 2024)
Purpose: This study examines how m-banking service quality, including efficiency, reliability, security, privacy, responsiveness, and communication, impacts customer satisfaction and loyalty.Research Methodology: Conducted in Indonesia, the research employs a quantitative approach with 135 respondents who have used m-banking services at least three times. Data were analyzed using Moderated Regression Analysis (MRA) through the SmartPLS 4.0 software.Results: The results indicate a significant and positive impact of m-banking service quality on customer satisfaction (R² = 50.8%) and loyalty (R² = 36.3%). Key statistical analyses, including validity tests (Cronbach’s alpha > 0.6) and hypothesis testing with t-statistics (t > 1.96, p < 0.05), affirm the reliability of the findings. However, the study is limited by its reliance on self-reported data and its geographical scope, which may not fully represent broader market behaviors.Conclusions: This study evaluates how the quality of m-banking services impacts customer satisfaction and loyalty. The results show that service quality positively affects both satisfaction and loyalty, with factors like transaction efficiency, trust, security, and accessibility playing key roles. Meeting or exceeding customer expectations enhances long-term loyalty and encourages recommendations.Limitation: The study’s limitations include a sample confined to respondents with prior experience using mobile banking (m-banking) services, thereby excluding potentially insightful perspectives from new or infrequent users.Contribution: This research contributes to the growing field of digital banking by highlighting service quality's role in fostering satisfaction and loyalty. It introduces a refined model that aligns with the ongoing digitalization in the banking sector, offering insights for future enhancements in customer-centric innovations and strategic implementations in m-banking.